Application of transient pulses on power supply cables by using commercial of the shelf components - J. Hagmann; L.-O. Fichte; S. Dickmann; M. Schaarschmidt; S. Potthast (Advances in Radio Science, 2010)
This paper deals with the development of ultra wide band pulse devices using merchantable hardware. The major goal is to create wide band transients and pulses with simple electronic equipment and to achieve high voltages and low pulse rise times. The propagation of these signals on common power lines are examined to analyse and forecast the effects on attached devices.